Sustainability Reporting and Organizational Impression Management – An Analysis of Selected Issues Based on Case Studies from the Energy Sector Companies - Agnieszka JANIK; Adam RYSZKO; Marek SZAFRANIEC (Communications of International Proceedings, 2020)
This paper presents the results of an analysis of selected issues related to organizational impression management in the context of sustainability reporting. The research was based on eight case studies of sustainability reports from the energy sector companies and, in particular, it concerned issues related to greenhouse gas emissions and circular economy (GHG and CE issues). The analysis focused on the disclosures which refer directly to GHG and CE issues in the statements from senior decision-makers. These statements were confronted with the occurrence of GHG and CE issues in the list of material topics, the scope of information and indicators related to GHG and CE issues, the accuracy of information related to GHG and CE issues, as well as the clarity and comparability of relevant information.
Keywords: Sustainability reporting; impression management; energy sector; case study.